Measurement Of Nutritional Status Of Preschool Children And Healthy Food Education At Aisiyah Karangjati Kindergarten Bantul Yogyakarta - hutasoit, masta (Sahabat Publikasi Kuu, 2024)
Pre-school age children (3-6 years) are in the golden period for growth and development. Children in growing need adequate nutrition. Data on undernutrition and malnutrition in Yogyakarta province amounted to 15.50%. Measurement of nutritional status is carried out based on anthropometric indicators. Most children's nutritional status measurements were at normal nutritional status of 59.6%, overweigh of 21.2% and risk of overweigh of 19.2%. In addition to measuring nutritional status, we also provided health advice on healthy nutrition for preschool children (3 to 6 years old). From the commitment results, it can be concluded that the nutritional status of the children in Aishiya Kindergarten was within a more normal range and that advice on healthy nutrition could enhance the children's understanding of healthy nutrition